PENGARUH BELAJAR MENGGUNAKAN BRAIN GAME TERHADAP HASIL BELAJAR ISTILAH–ISTILAH ALAT REPRODUKSI WANITA PADA MAHASISWA AKADEMI KEBIDANAN DR. SOEBANDI – JEMBER TAHUN 2012 - Musia (Jurnal Kesehatan dr. Soebandi, 2013)
Lack of faculty creativity in using the media or the less precise method of learning will affect the interes and motivasi students in upper division courses, especially in anatomy courses considering this course is the subject of science and the number of memorization that must be mastered by student. And the anatomy lessonsare still many students who get the vallueof C and D. This is what should be a concern for a teacher, to menrubah and improve the method or medium of learning, which can attract students’ interest in learning, and change of learning environment that is too monotonous, one of which is the learning method, Brain Game. Is there any problem in this study Brain Game is to know the results of studying the terms female reproductive organs after administrations of learning methods using the Brain Game on students AKBID dr.jember Soebandi Academic Year 2010 – 2011. In this case study design using pre Eksperimental one group pretest-postest design. Samples taken using total sampling technique. Research result showed after the method of Brain Game in student level I.